1985
DOI: 10.1002/pssb.2221270147
|View full text |Cite
|
Sign up to set email alerts
|

Specific Heat of Si and Ge

Abstract: The thermal properties such as specific heat, thermal expansion coefficient, etc. of tetrahedrally covalent crystals have been experimentally studied (for instance, see /1, 2/), and the negative thermal expansion at low temperature

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…The limiting low temperature value of was obtained. For the bulk crystal, the calculated θ D ≈ 413 K. This is in reasonable agreement with, but somewhat higher (by ≈ 10%) compared to, the observed standard value of θ D for Ge, which is 374 K. It was found that the θ D for the Ge NW is about a factor of 1.57 lower than that of the Ge bulk crystal. This is an important result showing significant softening of low-frequency long-wavelength acoustic phonons and the associated elastic constants.…”
Section: Discussionsupporting
confidence: 78%
“…The limiting low temperature value of was obtained. For the bulk crystal, the calculated θ D ≈ 413 K. This is in reasonable agreement with, but somewhat higher (by ≈ 10%) compared to, the observed standard value of θ D for Ge, which is 374 K. It was found that the θ D for the Ge NW is about a factor of 1.57 lower than that of the Ge bulk crystal. This is an important result showing significant softening of low-frequency long-wavelength acoustic phonons and the associated elastic constants.…”
Section: Discussionsupporting
confidence: 78%
“…The thermal coefficient α , is found to be ~7.2 × 10 −5 eV/K for the low energy transition peak and slightly increases to 8.9 × 10 −5 eV/K for the high energy transition peak. This value of α is larger by approximately one order of magnitude as compared to that of the bulk semiconductor 27 . It can be seen that the thermal coefficient of the fitted peaks are dependent on their respective emission energy.…”
Section: Resultsmentioning
confidence: 77%